Effect of aluminum on the primary carbides of a hypereutectic high chromium cast iron. Issue 1 (16th January 2015) - Zhi, X.; Han, Y.; Lui, J.
<x xml:space="preserve">Abstract</x> The effect of aluminum on the primary M7C3 carbides of a hypereutectic high chromium cast iron containing 4.0 wt% carbon and 20.0 wt% chromium was studied by means of optical microscopy, scanning electron microscope (SEM), energy dispersive X‐ray spectrometry (EDX), water quenching, and differential thermal analysis (DTA). Compared with specimen without aluminum addition, the primary carbides were all refined when different amount of aluminum was added into the melts, but the primary carbides in specimen with 0.3 wt% aluminum were the finest. With the addition of aluminum, aluminum element enriched at the boundary of primary carbides during solidification and was beneficial for the refinement of primary carbides. However, the increase of primary carbide growth time with the increase aluminum content had adverse effect on the refinement of the primary carbides. The comprehensive influence of those two factors leaded to the result that the primary carbides in specimen 1 with 0.3 wt% aluminum were the finest.